Researching the Use of Mindfulness for Stress reduction and Well Being in the Fire Service - Abbott, Claire (2017)
ABSTRACT Introduction: Stress is a growing concern for society today and in organisations this is leading to increased mental and physical illness and absenteeism. Mindfulness has been extensively researched and proven to be effective for stress reduction in medical and clinical settings; there is growing interest in using mindfulness-based interventions (MBIs) in organisations but little research has been done on its effectiveness in these settings. The fire service is an organisation that experiences high levels of stress, but very few mindfulness studies have been carried out in this area. My study is the first to use a longitudinal mixed methods approach to explore how mindfulness training impacts of the well-being of fire service personnel. Aims: (A) To determine whether mindfulness training reduces stress levels and increases well-being of fire service personnel. (B) To explore and compare how two different types of mindfulness training impact on participants’ well-being. (C) To examine participants’ views on mindfulness and the aspects of their experience that have led to changes in well-being. Method: This study will use a longitudinal sequential mixed methods approach (quantitative outcomes and qualitative interviews and focus group) to explore how two different mindfulness interventions (app and course) impact on the stress and well-being levels of fire service personnel. Results: The quantitative results of this small-scale study showed that stress levels reduced and well-being levels increased after the participants had completed the mindfulness training. Qualitative data contributed to the explanation of these results, giving a deeper understanding of which aspects of the training led to these changes. Discussion: Evaluating how mindfulness training impacts on the well-being of fire service personnel, and the feasibility of implementing a larger study on mindfulness will contribute to the growing awareness of a need to address mental health issues of emergency personnel, to increase resilience and prevent long-term stress-related absenteeism.